2002
DOI: 10.1098/rstb.2001.0991
|View full text |Cite
|
Sign up to set email alerts
|

Multiple states in river and lake ecosystems

Abstract: Nonlinear models of ecosystem dynamics that incorporate positive feedbacks and multiple, internally reinforced states have considerable explanatory power. However, linear models may be adequate, particularly if ecosystem behaviour is primarily controlled by external processes. In lake ecosystems, internal (mainly biotic) processes are thought to have major impacts on system behaviour, whereas in rivers, external (mainly physical) factors have traditionally been emphasized. We consider the hypothesis that model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 72 publications
2
117
0
Order By: Relevance
“…Such "toy models" -based on simple coupled ODEs/PDEs or cellular automata, and often relying on simplified representations of lumped physical processes -parsimoniously represent the feedbacks and nonlinearities that drive co-evolutionary relationships, remaining simple enough to allow analytical exploration, deployment in stochastic frameworks without requiring large computing infrastructure, and accessibility (Kumar, 2011). These kinds of models have been successfully used to predict threshold-like transitions in ecology -for example between oligotrophic and eutrophic conditions in shallow lakes (Dent et al, 2002;Scheffer et al, 2001), vegetated and desertified conditions in semi-arid shrublands (Kefi et al, 2007;Rietkerk et al, 2002), between grass-or shrub-dominated semi-arid rangelands (D'Odorico et al, 2006;Okin et al, 2009), or even between conditions in which mussel colonies can or cannot establish (van de Koppel et al, 2005). Efforts in resource economics have demonstrated that low-dimensional models that couple human and natural systems can have significant explanatory power (Taylor and Brander, 1998), for example, by interpreting the specific interactions and conditions that explain the collapse of the monument-building culture on Easter Island (Fig.…”
Section: Co-evolutionary Modelingmentioning
confidence: 99%
“…Such "toy models" -based on simple coupled ODEs/PDEs or cellular automata, and often relying on simplified representations of lumped physical processes -parsimoniously represent the feedbacks and nonlinearities that drive co-evolutionary relationships, remaining simple enough to allow analytical exploration, deployment in stochastic frameworks without requiring large computing infrastructure, and accessibility (Kumar, 2011). These kinds of models have been successfully used to predict threshold-like transitions in ecology -for example between oligotrophic and eutrophic conditions in shallow lakes (Dent et al, 2002;Scheffer et al, 2001), vegetated and desertified conditions in semi-arid shrublands (Kefi et al, 2007;Rietkerk et al, 2002), between grass-or shrub-dominated semi-arid rangelands (D'Odorico et al, 2006;Okin et al, 2009), or even between conditions in which mussel colonies can or cannot establish (van de Koppel et al, 2005). Efforts in resource economics have demonstrated that low-dimensional models that couple human and natural systems can have significant explanatory power (Taylor and Brander, 1998), for example, by interpreting the specific interactions and conditions that explain the collapse of the monument-building culture on Easter Island (Fig.…”
Section: Co-evolutionary Modelingmentioning
confidence: 99%
“…Ecological or hydromorphological responses to flooding (rapid recovery or shift to a different form) have been conceptualized over recent decades, invoking ideas including stability, sensitivity, resistance, resilience, stability domains separated by thresholds, nonlinear dynamics and complexity theory (Leopold and Wolman, 1957;Holling, 1973;Schumm, 1979;Phillips, 1992;Downs and Gregory, 1995;Gunderson, 2000;Stallins, 2006). By combining empirical observations and conceptual models, the mechanisms underlying these behaviours are being elucidated, such as the roles of feedback mechanisms and thresholds in maintaining or switching between alternative system states (Dent et al, 2002).…”
Section: Eco-hydromorphic Responses To Environmental Changementioning
confidence: 99%
“…4). Rivers and streams have generally been considered as open systems, subject to strong external environmental influences (38). We can therefore infer that it is highly likely that the kind of internal spatial feedbacks demonstrated in our study may play an even more important role in other ecosystem types where the effect of template heterogeneity is not as strong.…”
Section: Relative Influences Of Exogenous Factors and Internal Spatialmentioning
confidence: 86%